(untitled) (GYMNASIUM, 2011)
Back pain (and I refer to the lumbar area especially) can have multiple causes, disc herniation being one of them. Goal – Optimizing the recovery from lumbar disc hernia through kinetic means The theoretic objective tackles the specific problem in the recovery process, the improvement of symptoms induced by the lumbar disc herniation .